Probing the Diversity of Polycomb and Trithorax Proteins in Cultured and Environmentally Sampled Microalgae - Zhao, Xue; Deton Cabanillas, Anne Flore; Veluchamy, Alaguraj; Bowler, Chris; Vieira, Fabio Rocha Jimenez; Tirichine, Leila (Frontiers in Marine Science, 2020)
Polycomb (PcG) and Trithorax (TrxG) complexes are two evolutionarily conserved epigenetic regulatory components that act antagonistically to regulate the expression of genes involved in a plethora of biological processes. Both complexes were studied mainly in multicellular organisms with highlighted roles in development and their discovery in recent years in single-cell species raises important questions in respect to the extent of their existence, their role and significance in unicellular species. Using a highly sensitive method for the detection and annotation of protein domain architecture called eDAF, our work reports an unprecedented diversity of Polycomb and Trithorax groups of proteins from lab cultures and the environment at broad scale in Tara Oceans genomics datasets and shows significant correlations with environmental factors measured during the expedition. Both complexes are histone writers responsible for the deposition of important key histone marks including H3K27me3 and H3K4me3 deposited by Polycomb and Trithorax complexes respectively. To better understand the role of these proteins, we used the model diatom Phaeodactylum tricornutum to profile genome wide a trithorax deposited mark, H3K4me3 and showed its conserved role as an activating mark. We compared its profile with previously published marks among which the antagonizing Polycomb associated mark H3K27me3 which we found to co-occur in an exclusive manner with a balanced expression suggesting a bivalency. Our work puts under the spot light these complexes which were thought to be present only in multicellular organisms and highlights the ancestral function of these complexes in a broader evolutionary context than is currently appreciated.